Restrictive policy impacts in emerging economies - Chokri Zehri (Cogent Economics & Finance, 2020)
The policy responses to capital flows in emerging markets are multiple. However, capital inflow controls, if applied sufficiently broadly, can buttress all other policies by limiting the volume of capital inflows and address balance sheet vulnerabilities. The study analyzes the effects of capital controls (CC) domestically and internationally. Applied to 24 emerging economies (EEs) from 2009 to 2016, a panel vector autoregression model using a quarter dataset provides further evidence on these effects. Domestically, the results show that following the 2008 financial crisis, strengthening CC may support policymakers' actions to improve their macroeconomic policies. Unpredictably, there is no relationship founded between CC and international reserves accumulation. However, a combination of controls and reserves are needed to manage well the volatile capital flows. Internationally, restrictions on capital flows may cause spillovers between countries introducing controls and neighboring countries. These multilateral effects raise the challenge of optimal policy coordination.
Keywords: F32; F41; G15; F42; 330; capital; flows; policy; restrictions; spillovers